Immune response to influenza A(H1N1)v in HIV-infected patients - Paola Sansonetti; Michela Sali; Massimiliano Fabbiani; Matteo Morandi; Rosa Martucci; Ali Danesh; Giovanni Delogu; Jesus Bermejo-Martin; Maurizio Sanguinetti; David Kelvin; Roberto Cauda; Giovanni Fadda; et al. (Journal of Infection in Developing Countries)
Introduction: HIV infection is considered a risk factor for severe outcomes of influenza A(H1N1)v infection. However, data on immune response against influenza A(H1N1)v virus in HIV-infected patients are lacking. Methodology: Data from seven HIV-positive and 14 HIV-negative patients infected with A(H1N1)v and from 23 HIV-positive and six HIV-negative asymptomatic controls were analyzed to evaluate the clinical picture, A(H1N1)v viral shedding, and the immune response against the virus. Results: Patients displayed mainly upper respiratory tract diseases (57.1%), while pneumonia was diagnosed only in HIV-negative patients (23.8% of subjects, of which 4.8% required intensive care unit admission). At day seven, 29% of HIV-infected patients were still positive for A(H1N1)v by RT-PCR on nasopharyngeal swabs. Interestingly, a persistence of CXCL10 secretion at high level and lower IL-6 levels was observed in HIV-positive subjects. The geometric mean haemagglutination inhibition titer (HI-GMT) and anti-influenza IgM levels were lower in HIV-positive individuals while anti-influenza IgG levels remained similar in the two groups. Conclusions: The immune impairment due to HIV infection could affect A(H1N1)v clearance and could lead to a lower antibody response and a persistent secretion of CXCL10 at high levels. However, the lower IL-6 secretion and treatment with highly active antiretroviral therapy (HAART) could result in a milder clinical picture.